Does peak wall stress correlate better with abdominal aortic aneurysm expansion than aortic diameter? - Abdul Rahman, Mohd Norhisham Azmi; Gulati, Sumit M.; Mekako, A. I.; McCollum, Peter Thomas; Chetter, Ian Clifford (Oxford Academic, 2007)
Objective: Level 1 evidence clearly supports ultrasound surveillance in abdominal aortic aneurysm (AAA) <5.5 cm in maximum AP diameter, with scanning interval set according to the size of aneurysm. Larger aneurysms tend to expand at a greater rate than smaller aneurysms. However, AAA expansion is variable and difficult to predict, and size may not always predict expansion. We aimed to assess whether peak wall stress (PWS) measured through finite element analysis, correlates better with AAA expansion. Methods: Thirty-eight patients, 31 men, median age of 76.5 (range 54–93) years, currently under AAA surveillance were studied. All patients underwent abdominal CT scan to characterise the aneurysms and measure PWS through finite element analysis. Expansion rates were derived from sequential ultrasound scans. Correlation between PWS and expansion rate, as well as between size and expansion rate was analysed using Spearman Test (SPSS for Windows v14). Results: Mean aortic diameter was 4.68±0.74 cm and mean PWS was 0.41±0.14 MPa. Spearman rank order correlation coefficient (rs) of PWS and AAA expansion rate was 0.28 (P=0.08). Spearman rank order correlation coefficient (rs) of aorta AP diameter and AAA expansion rate was 0.17 (P=0.30). Conclusions: In this cohort of patients the correlation between PWS and AAA expansion rate was not significant however, the correlation was superior to that between AAA diameter and expansion rate, and this deserves further investigation.